Gondomono (Hedycium spicatum) Ethanol Exstract Anti-Proliferation, Apoptosis and P53 Cancer Cell Line - Nur Rahman (Humanistic Network for Science and Technology (HNST), 2021)
The incidence of cancer from year to year continues to increase. Some of the causes of this incident include an unhealthy lifestyle, smoking, a diet high in fat and low in fiber. The Gondomono plant (Hedychium spicatum) are the most studied species. Interesting compounds have been identified like coronarin D, which possesses antibacterial, antifungal and antitumor activities, as well as isocoronarin D, linalool and villosin that exhibit better cytotoxicity towards tumor cell lines than the reference compounds used, with villosin not affecting the non-tumor cell line. This study aims to obtain scientific evidence that Gondomono extract (Hedychium spicatum) is proven to be anti-cancer. The impact obtained will be utilized by local Indonesian plants that can be processed or produced as functional food and herbal medicine for anti-cancer bioactivity toxicity with various tests including the making gondomono (Hedycium spicatum) flour, ethanol extraction method, insilico analysis and Gas Chromatography-Mass Spectrometry (GC-MS) analysis, then the second stage test, namely the MTT test, P53 test and apoptosis test. The research design was experimental. Gondomono extract when compared to anticancer ingredients was indeed very far away, gondomono extract was starting to be able to act as apoptosis, it requires a fairly high concentration, from 200 to 400 ppm. As conclusion, the higher the dose of gondomono extract, the higher the expression of p53 protein, the higher. Gondomono extract as a cancer cell killer requires a minimum dose of 368.51 ppm. Keywords: gondomono; Hedycium spicatum; anti-proliferasi; cancer cell line